2015
DOI: 10.1111/pce.12618
|View full text |Cite
|
Sign up to set email alerts
|

Embolism spread in the primary xylem of Polystichum munitum: implications for water transport during seasonal drought

Abstract: Xylem network structure and function have been characterized for many woody plants, but less is known about fern xylem, particularly in species endemic to climates where water is a limiting resource for months at a time. We characterized seasonal variability in soil moisture and frond water status in a common perennial fern in the redwood understory of a costal California, and then investigated the consequences of drought-induced embolism on vascular function. Seasonal variability in air temperature and soil w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
2
7
0
1
Order By: Relevance
“…The stem xylem of the two Selaginella species was found to be surprisingly resistant to embolism formation, contrary to our initial New Phytologist hypothesis based on published xylem traits, hydraulic function and habitat preferences of these two Selaginella species. Highly resistant xylem (xylem in which embolism does not form until at least À 5 MPa) has been described for the stipes of several fern species (Pittermann et al, 2011;Brodersen et al, 2014Brodersen et al, , 2016, and here we further indicate two Selaginella species with xylem that does not embolize until À 3.0 MPa. Such high xylem resistance to embolism formation in both Selaginella species may be due to relatively thick interconduit pit membranes.…”
Section: Researchsupporting
confidence: 76%
See 1 more Smart Citation
“…The stem xylem of the two Selaginella species was found to be surprisingly resistant to embolism formation, contrary to our initial New Phytologist hypothesis based on published xylem traits, hydraulic function and habitat preferences of these two Selaginella species. Highly resistant xylem (xylem in which embolism does not form until at least À 5 MPa) has been described for the stipes of several fern species (Pittermann et al, 2011;Brodersen et al, 2014Brodersen et al, , 2016, and here we further indicate two Selaginella species with xylem that does not embolize until À 3.0 MPa. Such high xylem resistance to embolism formation in both Selaginella species may be due to relatively thick interconduit pit membranes.…”
Section: Researchsupporting
confidence: 76%
“…In Selaginella species it is likely that resistant xylem evolved because of inefficient stomatal closure, as a means of prolonging the period of time plants can draw upon cortical water after the imposition of high VPD and before the formation of lethal embolism. Given that resistant xylem has been observed in mesic species from the two earliest diverging extant vascular land plant clades (Pittermann et al, 2011;Brodersen et al, 2014Brodersen et al, , 2016, it is tempting to speculate that the earliest xylem in the common ancestor of vascular plants, and possibly the earliest plants on land, was equally resistant to embolism formation. We do not yet know what precise features of the xylem of Selaginella allow it to be so resistant to embolism formation.…”
Section: Researchmentioning
confidence: 99%
“…7). Brodersen and Pittermann (2016) found similar patterns of cellular collapse within the cortex and around the vascular tissue of fern stipes during desiccation, as well as highly resistant xylem conduits using similar methods. It is therefore noteworthy that the cortex may be playing a functionally similar role in two divergent groups (i.e., ferns and conifers) before the formation of woody tissue in the seedling stage.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies showed that there was little relationship between leaf hydraulic conductance and g s in some species. Juglans regia treated with abscisic acid failed to open stomata, and an almost 50% loss of hydraulic conductance in Polystichum munitum minimally influenced stomatal conductance [35,37].…”
Section: Regulation Of Stomatal Conductancementioning
confidence: 99%